2011
DOI: 10.1007/s11771-011-0855-7
|View full text |Cite
|
Sign up to set email alerts
|

Features of pipe transportation of paste-like backfilling in deep mine

Abstract: Based on the pipe transportation of paste-like backfilling system of a certain deep coal mine, its dynamics process was simulated and analyzed. A two-dimensional dynamic model of extraordinary deep and lone pipe was built by GAMBIT, on the basis of which the simulation was done by implicit solver of FLUENT 2ddp. The results show that hydraulic loss of pipe transportation is less than the pressure produced by gravity, which means the backfilling material can flow by itself. When the inlet velocity is 3.2 m/s, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…The velocity variation trend shows an increase in the vertical pipe and a decrease in the horizontal pipe; the maximum velocity occurs at the elbow of the pipe. The mine backfill experience of South Africa indicated that the velocity of the horizontal pipe should not exceed 4 m/s [19]. Therefore, the two proportioning schemes both meet the requirements of backfill.…”
Section: Recoverabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The velocity variation trend shows an increase in the vertical pipe and a decrease in the horizontal pipe; the maximum velocity occurs at the elbow of the pipe. The mine backfill experience of South Africa indicated that the velocity of the horizontal pipe should not exceed 4 m/s [19]. Therefore, the two proportioning schemes both meet the requirements of backfill.…”
Section: Recoverabilitymentioning
confidence: 99%
“…The mine backfill experience of South Africa indicated that the velocity of the horizontal pipe should not exceed 4 m/s [19]. Therefore, the two proportioning schemes both meet the requirements of backfill.…”
Section: Recoverabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, paste-like tailings slurry (PLTS) was simplified as a Bingham plastic fluid, whose flow properties were time-independent, and the existing empirical formulas for calculating the hydraulic gradient of a paste-like flow were derived based on the time-invariant Bingham model [7]. However, an increasing number of studies have shown that the rheological characteristics of PLTS are consistent with those of a pseudo-plastic fluid, and the existing empirical formulas are optimal for calculating the error and for small applications [8].…”
Section: Introductionmentioning
confidence: 99%
“…Backfill mining technology plays a significant role in environmental protection and the prevention of water resource pollution [1,2]. Therefore, it is being widely and intensively employed in the global mining industry.…”
Section: Introductionmentioning
confidence: 99%